SCHOOL BULLYING, CYBERBULLYING AND STUDENTS’ LIFE SATISFACTION IN A KLANG VALLEY NGO SCHOOL - YOGITHA VATHANA, KANAN; Ooi, Pei Boon; Ho, Meng Chuan; Voon, Siok Ping; Sunwei, Yeoh (Quantum Academic Publisher Enterprise, 2024)
This study addresses the critical interplay between bullying, cyberbullying, and adolescent life satisfaction, recognizing their profound impacts on various aspects of adolescents' lives beyond individual well-being, including community dynamics and psychological development. Conducted among 152 respondents aged 13 to 17 from a non-governmental organization (NGO) school in the Klang Valley, the study utilized comprehensive survey tools such as the Olweus Bully/Victim Questionnaire (OBVQ), Cyberbullying Perpetration Scale (CBP), Cyberbullying Victimization (CBV), and Satisfaction with Life Scale (SWLS) to collect and analyze data. Results highlight a significant relationship between school bullying, cyberbullying, and satisfaction with life, underscoring the need for multifaceted interventions that extend beyond mere awareness-raising efforts. It emphasizes the importance of promoting personal and social resources, including optimism and empathy, through targeted programs aimed at enhancing overall satisfaction and quality of life among adolescents. Additionally, direct engagement with perpetrators is advocated to raise awareness of the detrimental impact of their actions on victims' well-being. These findings underscore the urgency of addressing bullying and cyberbullying comprehensively to safeguard adolescent mental health and well-being.